Organizational Communication in the Digital Era: Work From Anywhere Policies - Mulzakir, Mulzakir; Anggraeni, Eliza Dwi; Yusuf, Febiola Aditya (Universitas Mercu Buana, 2024)
An example of implementing Working From Anywhere in a government agency, namely the Ministry of Finance which is a pioneer in implementing new modern work patterns through the use of digital communication technology. The implementation of Work From Anywhere is part of the Ministry of Finance's strategic initiative, which provides flexibility in work locations during certain periods by maximizing information and communication technology to increase and maintain employee productivity. This research aims to make an academic contribution by adding knowledge to the research that has been carried out. The method used in this research is literature study by collecting information through scientific journals and books which are analyzed based on existing problems. Sources of information are obtained from research conducted by credible researchers and writers. Implementing Work From Anywhere has become an important option for many organizations post the Covid-19 pandemic, driven by technological advances and the need for flexibility in the workplace. Digital Communication Technology plays a key role in supporting the implementation of Work From Anywhere Policies, allowing employees to stay connected without having to be physically in the office location and the implementation of Work From Anywhere has great potential to increase work effectiveness in the digital era. This literature study was supported by Ministry of Communication and Information Technology of The Republic of Indonesia and Universitas Sumatera Utara. We thank our lecturer and colleagues from Universitas Sumatera Utara who provided insight and expertise that greatly assisted the literature study, with all of the interpretations/conclusions of this paper.